Copper aluminate nanosheet, preparation method of copper aluminate nanosheet, polypropylene-copper aluminate composite material and preparation method and application of polypropylene-copper aluminate composite material

By introducing copper aluminate nanosheets into polypropylene to form polypropylene-copper aluminate composite, the problem of polypropylene is solved, and efficient flame retardant performance is achieved, delaying the ignition time and reducing the peak heat release value.

CN119569090APending Publication Date: 2025-03-07TAIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411884058.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Polypropylene materials are flammable and produce a large amount of heat during combustion, resulting in flame spread and ‘secondary fire’, which limits their application scope. The flame retardant performance in existing modification technologies is still poor.

Method used

Copper aluminate nanosheets are used as flame retardant and prepared by co-precipitation and calcination, and melt blending is combined with polypropylene to form a polypropylene-copper aluminate composite material.

Benefits of technology

Due to its two-dimensional structure and large surface area, copper aluminate nanosheets can effectively form a heat insulation layer, delay the ignition time, significantly improve the flame retardant performance of polypropylene, low peak heat release and excellent flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569090A_ABST
    Figure CN119569090A_ABST
Patent Text Reader

Abstract

The invention provides a copper aluminate nanosheet, a preparation method of the copper aluminate nanosheet, a polypropylene-copper aluminate composite material and a preparation method and application of the polypropylene-copper aluminate composite material, and belongs to the technical field of flame-retardant materials. The preparation method of the copper aluminate nanosheet comprises the following steps: mixing soluble copper salt, soluble aluminum salt, water and an alkaline solution, and carrying out coprecipitation reaction to obtain a precipitation product; and calcining the precipitation product to obtain the copper aluminate nanosheet. According to the copper aluminate nanosheet (CuAl2O4) provided by the invention, the CuAl2O4 nanosheet has a nano-sized structural micro-area, so that the CuAl2O4 nanosheet plays a role similar to heat insulation in a combustion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant materials, and specifically relates to a copper aluminate nanosheet and a preparation method thereof, a polypropylene-copper aluminate composite material and a preparation method and application thereof. Background Art

[0002] According to their hot melt properties, polymers can be divided into thermoplastic polymers (such as polyethylene, polypropylene, polystyrene and polyurethane) and thermosetting polymers (such as epoxy resins, unsaturated polyester resins and linear phenolic resins). Thermoplastic polymer composites have high plasticity, corrosion resistance and recyclability. They are widely used in industry, agriculture and science and technology, and occupy a very important position in contemporary and future international competition. Among them, polypropylene (PP) is a semi-crystalline thermoplastic polymer with excellent performance. It is generally obtained by polymerization of propylene monomers and has a molecular weight of hundreds of thousands. Its melting temperature is around 189°C and its density is about 0.9g / cm 3 As one of the world's top five general-purpose plastics, PP has good mechanical properties, excellent heat resistance, corrosion resistance and good processing performance, and is widely used in home appliances, new energy vehicles, food packaging, construction and other fields.

[0003] In recent years, the plastic products industry has developed rapidly. However, since PP materials are all-aliphatic hydrocarbon materials, they are composed of only two elements, C and H. The limiting oxygen index (LOI) of pure PP is only 17.4%. It is flammable, and it is not easy to form carbon during combustion, and it is accompanied by serious melting droplets. In some fields with special requirements for fire retardancy, PP materials cannot meet their use standards; in addition, PP will generate a lot of heat when it burns, and it is easy to cause melting drops and cast fire, causing the flame to spread to other materials, causing "secondary fires", which greatly limits its application range. In order to prepare PP with high-efficiency flame retardant properties, it can be blended, doped or grafted by physical or chemical methods. For example, blending modification with polyethylene (PE), ethylene-propylene rubber (EPR), etc., doping modification by adding flame retardants such as hydrated magnesium oxide, bis (2,3-dibromopropyl) fumarate and antimony trioxide, and grafting modification by grafting maleic anhydride, acrylic acid, etc., but the flame retardant properties of modified PP in the prior art are still poor. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a copper aluminate nanosheet and a preparation method thereof, a polypropylene-copper aluminate composite material and a preparation method and application thereof. The copper aluminate nanosheet provided by the present invention has good flame retardant properties, and the polypropylene-copper aluminate composite material prepared by using the copper aluminate nanosheet as a flame retardant has a low heat release peak, effectively delays the ignition time, and has excellent flame retardant properties.

[0005] In order to achieve the above object, the present invention provides the following scheme:

[0006] The present invention provides a method for preparing copper aluminate nanosheets, comprising the following steps:

[0007] Mixing a soluble copper salt, a soluble aluminum salt, water and an alkaline solution to perform a coprecipitation reaction to obtain a precipitated product;

[0008] The precipitation product is calcined to obtain the copper aluminate nanosheets.

[0009] Preferably, the molar ratio of copper in the soluble copper salt to aluminum in the soluble aluminum salt is 1:(1.5-3).

[0010] Preferably, the coprecipitation reaction is carried out at a temperature of 80 to 150° C. and for a time of 0.5 to 2 h.

[0011] Preferably, the alkaline solution comprises a solution of an alkali metal hydroxide.

[0012] Preferably, the calcination temperature is 500-800° C. and the calcination time is 2-6 hours.

[0013] The present invention provides copper aluminate nanosheets prepared by the preparation method described in the above scheme, wherein the copper aluminate nanosheets have a sheet diameter of 30 to 60 nm and a thickness of 5 to 15 nm.

[0014] The invention provides a polypropylene-copper aluminate composite material, comprising a polypropylene matrix and copper aluminate nanosheets dispersed in the polypropylene matrix; the copper aluminate nanosheets are the copper aluminate nanosheets described in the above scheme.

[0015] Preferably, the mass of the copper aluminate nanosheets is 0.2-10% of the mass of the polypropylene-copper aluminate composite material.

[0016] The present invention provides a method for preparing the polypropylene-copper aluminate composite material of the above scheme, comprising the following steps: melt-blending a polypropylene matrix and copper aluminate nanosheets to obtain the polypropylene-copper aluminate composite material.

[0017] The present invention provides application of the polypropylene-copper aluminate composite material described in the above scheme or the polypropylene-copper aluminate composite material prepared by the preparation method described in the above scheme in the field of flame retardancy.

[0018] The invention provides a method for preparing copper aluminate nanosheets, comprising the following steps: mixing a soluble copper salt, a soluble aluminum salt, water and an alkaline solution, performing a coprecipitation reaction, and obtaining a precipitation product; and calcining the precipitation product to obtain the copper aluminate nanosheets. The invention can adjust and control the pH value of the solution to 12 by adding an alkaline solution, so that the solution can perform a coprecipitation reaction under alkaline conditions, and can ensure that the required chemical reaction proceeds smoothly, thereby generating the target product copper aluminate nanosheets. The copper aluminate nanosheets (CuAl2O4) provided by the invention play a similar role of heat insulation during the combustion process due to the nano-sized structural micro-regions. In addition, the copper aluminate nanosheets mainly play the role of a heat insulation layer during the flame retardant process. Due to their two-dimensional structure, the copper aluminate nanosheets can more effectively block the transfer of heat and the diffusion of oxygen. When combustion occurs, the copper aluminate nanosheets can be quickly dispersed in a polymer matrix to form a dense protective layer, thereby delaying or preventing the combustion. The copper aluminate nanosheets obtained by the present invention and the nanoparticles in the prior art differ in flame retardant efficiency. The copper aluminate nanosheets can form a heat insulation layer more effectively due to their two-dimensional structure and large surface area, thus having higher flame retardant efficiency.

[0019] The present invention provides a polypropylene-copper aluminate composite material, comprising a polypropylene matrix and copper aluminate nanosheets dispersed in the polypropylene matrix. The flame retardant effect of the copper aluminate nanosheets (CuAl2O4) in the present invention may be related to the flame retardant effect and chemical reaction of the nanosheets during the combustion process. On the one hand, the nano-sized structural micro-region plays a similar role of heat insulation; on the other hand, during the combustion process, CuAl2O4 may react with the free radicals generated by the decomposition of PP, thereby interrupting the combustion chain reaction and slowing down the combustion rate. At the same time, the addition of CuAl2O4 may also promote the formation of a stable carbon layer in PP during the combustion process. The formation of the carbon layer can isolate oxygen and heat, further slowing down the combustion process. The results of the embodiment show that the copper aluminate nanosheets provided by the present invention have good flame retardant properties. The polypropylene-copper aluminate composite material prepared by using the copper aluminate nanosheets as a flame retardant has a low heat release peak, effectively delays the ignition time, and has excellent flame retardant properties.

[0020] In addition, the CuAl2O4 provided by the present invention, as an inorganic particle, can be dispersed in the polypropylene-copper aluminate composite material as a reinforcing phase. Through the interaction with the PP matrix material, the CuAl2O4 can bear part of the load and improve the tensile strength of the polypropylene-copper aluminate composite material. Further, the interface interaction between the CuAl2O4 and the PP matrix material may be enhanced, and a good interface bonding can effectively transfer the load and prevent the expansion of cracks, thereby improving the overall tensile strength of the polypropylene-copper aluminate composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0022] Figure 1 This is the XPS spectrum of CuAl2O4 nanosheets;

[0023] Figure 2 is the XRD pattern of CuAl2O4 nanosheets;

[0024] Figure 3 XRD standard card of CuAl2O4 (JCPDS No.33-0448);

[0025] Figure 4 HRTEM-EDS spectrum of CuAl2O4;

[0026] Figure 5 Typical stress-strain curves of PP and polypropylene-copper aluminate (PP-CuAl2O4) composites;

[0027] Figure 6 For PP and PP-CuAl2O4 composite materials at 35kW / m 2 Heat release rate curve when

[0028] Figure 7 Digital photos of the residues after cone calorimeter test, PP (a), PP / CuAl1 (b) and PP / CuAl10 (c). DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing copper aluminate nanosheets, comprising the following steps:

[0030] Mixing a soluble copper salt, a soluble aluminum salt and water, and performing a coprecipitation reaction under alkaline conditions to obtain a precipitated product;

[0031] The precipitation product is calcined to obtain the copper aluminate nanosheets.

[0032] Unless otherwise specified, the raw materials and equipment used in the present invention are commercially available products.

[0033] The invention mixes soluble copper salt, soluble aluminum salt, water and alkaline solution, performs coprecipitation reaction and obtains precipitation product.

[0034] In the present invention, the soluble copper salt preferably includes one or more of copper sulfate, copper chloride and copper nitrate; the soluble aluminum salt preferably includes one or more of aluminum chloride, aluminum sulfate and aluminum nitrate; the molar ratio of copper in the soluble copper salt to aluminum in the soluble aluminum salt is preferably 1:(1.5-3), and in the embodiment of the present invention, it can be specifically 1:1.5, 1:2 or 1:3. In the present invention, the mixing is preferably carried out under stirring; the stirring speed is preferably 300-800rpm, and in the embodiment of the present invention, it can be specifically 300rpm, 400rpm, 500rpm, 600rpm, 700rpm or 800rpm. In the present invention, the mixing temperature is preferably room temperature.

[0035] In the present invention, the mixing preferably comprises: mixing an aqueous solution of a soluble copper salt and an aqueous solution of a soluble aluminum salt, then dropping an alkaline solution, and maintaining the pH value of the mixed solution at 12. In the present invention, the concentration of the aqueous solution of the soluble copper salt is preferably 0.18 mmol / L; the concentration of the aqueous solution of the soluble aluminum salt is preferably 0.27 to 0.54 mmol / L, and in the embodiment of the present invention, it can be specifically 0.27 mmol / L, 0.36 mmol / L or 0.54 mmol / L; the volume ratio of the aqueous solution of the soluble copper salt to the aqueous solution of the soluble aluminum salt is preferably 1:1. In the present invention, the alkaline solution preferably comprises a solution of an alkali metal hydroxide; the alkali metal hydroxide preferably comprises sodium hydroxide.

[0036] In the present invention, when an alkaline solution is added dropwise to a mixed solution of a soluble copper salt and a soluble aluminum salt, the hydroxide ions (OH - ) begins to react with the cations in the mixed solution; since aluminum ions have a higher charge density and a stronger attraction to hydroxide ions, aluminum ions will preferentially react with hydroxide ions to form aluminum hydroxide (Al(OH)3) precipitation, Cu 2+ Also with OH - A reaction occurs to generate Cu(OH)2, and when the pH value is 12, Al(OH)3 will transform into aluminate.

[0037] The present invention can adjust and control the pH value of the solution to 12 by adding an alkaline solution, so that the coprecipitation reaction can be carried out under alkaline conditions, thereby ensuring that the required chemical reaction proceeds smoothly, thereby generating the target product copper aluminate nanosheets.

[0038] In the present invention, the temperature of the coprecipitation reaction is preferably 80-150°C, and in the embodiments of the present invention, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C; the time of the coprecipitation reaction is preferably 0.5-2h, and in the embodiments of the present invention, it can be 0.5h, 1h, 1.5h or 2h. The time of the coprecipitation reaction in the present invention is preferably calculated from the completion of the dropwise addition of the alkaline solution.

[0039] After the coprecipitation reaction is completed, the precipitated product is preferably filtered and then washed with deionized water for more than 3 times until the residual ions in the solution are washed away (the unreacted or residual Cu 2+ 、Al 3+ 、Na + and the corresponding acid radical ions are removed), and then dried. In the present invention, the drying temperature is preferably 150° C. and the drying time is preferably 12 hours.

[0040] After obtaining the precipitation product, the present invention calcines the precipitation product to obtain the copper aluminate nanosheets.

[0041] In the present invention, the calcination temperature is preferably 500-800°C, and in embodiments of the present invention, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C; the calcination time is preferably 2-6h, and in embodiments of the present invention, it can be 2h, 3h, 4h, 5h or 6h.

[0042] The present invention provides copper aluminate nanosheets prepared by the preparation method described in the above scheme. In the present invention, the diameter of the copper aluminate nanosheets is 30 to 60 nm, and in the embodiment of the present invention, it can be 30 nm, 40 nm, 50 nm or 60 nm; the thickness of the copper aluminate nanosheets is 5 to 15 nm. The average thickness is 10 nm.

[0043] The copper aluminate nanosheets (CuAl2O4) provided by the present invention play a similar role of heat insulation during the combustion process due to the nano-sized structural micro-regions. In addition, the copper aluminate nanosheets mainly play the role of a heat insulation layer during the flame retardant process. Due to its two-dimensional structure, the copper aluminate nanosheets can more effectively block the transfer of heat and the diffusion of oxygen. When combustion occurs, the copper aluminate nanosheets can be quickly dispersed in the polymer matrix to form a dense protective layer, thereby delaying or preventing the combustion. There is a difference in flame retardant efficiency between the copper aluminate nanosheets obtained by the present invention and the nanoparticles in the prior art. Due to its two-dimensional structure and large surface area, the copper aluminate nanosheets can more effectively form a heat insulation layer, thereby having a higher flame retardant efficiency.

[0044] The invention provides a polypropylene-copper aluminate composite material, comprising a polypropylene matrix and copper aluminate nanosheets dispersed in the polypropylene matrix; the copper aluminate nanosheets are the copper aluminate nanosheets described in the above scheme.

[0045] In the present invention, the mass of the copper aluminate nanosheets is preferably 0.2-10% of the mass of the polypropylene-copper aluminate composite material. In an embodiment of the present invention, it can be 0.2%, 1%, 2%, 5%, 8% or 10%.

[0046] The flame retardant effect of the copper aluminate nanosheets (CuAl2O4) in the present invention may be related to the flame retardant effect of the nanosheets and the chemical reaction during the combustion process. On the one hand, the nano-sized structural micro-regions play a role similar to heat insulation; on the other hand, during the combustion process, CuAl2O4 may react with the free radicals generated by the decomposition of PP, thereby interrupting the combustion chain reaction and slowing down the combustion rate. At the same time, the addition of CuAl2O4 may also promote the formation of a stable carbon layer in PP during the combustion process. The formation of the carbon layer can isolate oxygen and heat, further slowing down the combustion process. The results of the embodiments show that the copper aluminate nanosheets provided by the present invention have good flame retardant properties. The polypropylene-copper aluminate composite material prepared by using the copper aluminate nanosheets as a flame retardant has a low heat release peak, effectively delays the ignition time, and has excellent flame retardant properties.

[0047] In addition, the CuAl2O4 provided by the present invention, as an inorganic particle, can be dispersed in the polypropylene-copper aluminate composite material as a reinforcing phase. Through the interaction with the PP matrix material, the CuAl2O4 can bear part of the load and improve the tensile strength of the polypropylene-copper aluminate composite material. Further, the interface interaction between the CuAl2O4 and the PP matrix material may be enhanced, and a good interface bonding can effectively transfer the load and prevent the expansion of cracks, thereby improving the overall tensile strength of the polypropylene-copper aluminate composite material.

[0048] The present invention provides a method for preparing the polypropylene-copper aluminate composite material of the above scheme, comprising the following steps: melt-blending a polypropylene matrix and copper aluminate nanosheets to obtain the polypropylene-copper aluminate composite material.

[0049] Before the melt blending, the present invention preferably dries the polypropylene matrix and the copper aluminate nanosheets overnight, and then mixes them to obtain a mixed material. In the present invention, the drying temperature is preferably 60°C; the mixing speed is preferably 1000 rpm, and the mixing time is preferably 30 minutes.

[0050] In the present invention, the temperature of the melt blending is preferably 180° C., the time is preferably 5 to 8 minutes, and the rotation speed is preferably 50 rpm.

[0051] The present invention can achieve better material mixing of the polypropylene matrix and the copper aluminate nanosheets through melt blending. In this process, the PP melt similar to a solvent can better disperse the flame retardant CuAl2O4.

[0052] After the melt blending is completed, the present invention preferably extrude the obtained melt blended product, and then cut the extruded product into pieces every 25 cm and save them to obtain long strips of polypropylene-copper aluminate composite materials.

[0053] In the present invention, the elongated polypropylene-copper aluminate composite material is preferably granulated and dried to obtain a granular polypropylene-copper aluminate composite material for flame retardant performance testing.

[0054] In the present invention, the granulation rotation speed is preferably 50 rpm, and the granulation particle size is preferably 3-5 mm; the drying is preferably forced air drying; the drying temperature is preferably 60° C., and the drying time is preferably 1 hour.

[0055] In the present invention, the granular polypropylene-copper aluminate composite material is preferably injection molded to obtain a dumbbell-shaped polypropylene-copper aluminate composite material for mechanical property testing.

[0056] In the present invention, the mold temperature of the injection molding is preferably 80° C.; the total length of the dumbbell-shaped polypropylene-copper aluminate composite material is preferably 13 cm, and the thickness is preferably 3 mm.

[0057] The present invention preferably sprays a release agent on the mold to prevent the spline from getting stuck after injection molding. In the present invention, the release agent preferably includes one or more of a polypropylene wax release agent, an oleic acid amide release agent, and a silicone release agent; the polypropylene wax release agent preferably includes polypropylene wax powder (PP wax); the oleic acid amide release agent preferably includes an oleic acid amide slip agent; the silicone release agent preferably includes one or more of a polymer silicone powder, a silicone masterbatch, and a silicone powder. The present invention has no special requirements for the spraying amount of the release agent, and the amount well known in the art can be used.

[0058] The present invention provides the application of the polypropylene-copper aluminate composite material described in the above scheme or the polypropylene-copper aluminate composite material prepared by the preparation method described in the above scheme in the field of flame retardancy. In the present invention, it can be specifically applied to exterior wall insulation materials, interior decoration materials, housings and internal parts of electronic products such as televisions, computers, and mobile phones, and interior parts such as automobile dashboards, seats, and door panels.

[0059] In order to further illustrate the present invention, a copper aluminate nanosheet and a preparation method thereof, a preparation method and application of a polypropylene-copper aluminate composite material provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.

[0060] The sources of raw materials and equipment in the embodiments of the present invention are as follows:

[0061] Copper nitrate (Cu(NO3)2·3H2O), AR, Xiaxian Yunli Chemical Co., Ltd.; aluminum nitrate (Al(NO3)3·9H2O), AR, Xiaxian Yunli Chemical Co., Ltd.; sodium hydroxide (NaOH), AR, Cangzhou Haoxin Chemical Products Co., Ltd.; polypropylene (PP), Zhejiang Petrochemical Co., Ltd.

[0062] Natural convection precision oven, manufacturer Binder of Germany, model ED23; micro injection molding machine, manufacturer Wuhan Ruiming Experimental Instrument Co., Ltd., model SZS-20; cutting granulator, manufacturer Shiyan Precision Instrument Co., Ltd., model SY-6217-ZBQ-20; micro conical twin-screw extruder, manufacturer Wuhan Ruiming Experimental Instrument Co., Ltd., model SJZS-10A; high-speed dispersion grinder, manufacturer Hangzhou Qiwei Instrument Co., Ltd., model FS-1100D; precision electronic balance, manufacturer Sartorius, model SB124S; electric vacuum drying oven, manufacturer Shanghai Experimental Instrument Factory, model ZK-82BB; cone calorimeter, manufacturer Dongguan Zhongnuo Quality Inspection Instrument Equipment Co., Ltd., model ZY6243.

[0063] Example 1

[0064] Using a precision electronic balance, weigh chemically pure Cu(NO3)2·3H2O and Al(NO3)3·9H2O in a molar ratio of 1:2, dissolve them in appropriate amounts of deionized water, and prepare 0.18mM Cu(NO3)2·3H2O solution and 0.36mM Al(NO3)3·9H2O. Then mix the two solutions in a volume ratio of 1:1, stir evenly, and then drop 1M NaOH solution into the mixed solution. The mixed solution begins to precipitate. During the addition of NaOH solution, maintain a constant stirring speed of 500rpm and keep the pH value at around 12. After the addition is completed, heat the mixed solution to 100°C, continue stirring at a constant temperature for 1h, the color of the precipitate will gradually turn into dark brown, then filter the precipitate, wash with deionized water, and repeat for more than 3 times until the residual ions in the solution are washed away (the unreacted or residual Cu 2+ 、Al 3+ and Na + and the corresponding acid radical ions are removed) to obtain a precipitate.

[0065] The precipitate was dried in an electric vacuum drying oven at 150°C for 12 hours and then calcined at 600°C for 4 hours to obtain solid powder CuAl2O4 nanosheets. The diameter of the copper aluminate nanosheets was 30-60 nm and the average thickness was 10 nm.

[0066] Example 2

[0067] The PP-CuAl2O4 composite material was prepared by melt blending method, and the steps are as follows:

[0068] The CuAl2O4 nanosheets prepared in Example 1 were used as a flame retardant, and the flame retardant and PP pellets were dried overnight in a natural convection precision oven at 60°C, and then 0.2 g of the dried CuAl2O4 nanosheets and 99.8 g of the PP pellets were mixed on a high-speed dispersion grinder, i.e., the mass of the CuAl2O4 nanosheets was 0.2% of the total mass of the PP-CuAl2O4 composite material, the mixing speed was 1000 rpm, and the mixing was continued for 30 minutes to obtain a mixed material, which was collected for standby use;

[0069] The twin-screw extruder was powered on and preheating started. The temperatures of the conveying zone, melting zone (which is the main mixing zone) and extrusion zone of the extruder were set to 170°C, 180°C and 190°C, respectively. After the temperature stabilized, the mixed materials were added to the twin-screw extruder in batches for melt blending. The speed of the twin-screw extruder was maintained at 50 rpm. The melt blending time was 5 to 8 min. The extruded products were then cut off every 25 cm and stored to obtain long strips of PP-CuAl2O4 composite materials, recorded as PP / CuAl 0.2.

[0070] The long strip PP-CuAl2O4 composite material extruded by the twin-screw extruder was cut and granulated. The speed of the cutting granulator was 50 rpm / min. The sample strips extruded by the twin-screw extruder were added from the feed port of the cutting granulator. The granulation size (diameter) was about 3 to 5 mm. After further drying by blowing, the blowing temperature was 60°C and the time was 1 hour. The granulated PP-CuAl2O4 composite material was collected at the discharge port with a barrel to obtain a granular PP-CuAl2O4 composite material for flame retardant performance testing.

[0071] The granular PP-CuAl2O4 composite material obtained by granulation was injection molded, and the mold temperature was set to 80°C and the collector temperature was set to 200°C. Specifically, the granular product granulated by the cutting granulator was collected by a collector while hot, and then immediately injection molded by an injection molding machine. At the same time, a certain amount of mold release agent was sprayed on the mold to prevent the specimen obtained after injection molding from getting stuck. A dumbbell-shaped PP-CuAl2O4 composite material with a total length of 13 cm and a thickness of 3 mm was obtained for subsequent mechanical properties testing.

[0072] Embodiments 3 to 6

[0073] The preparation steps are the same as those in Example 2, except that the mass of the CuAl2O4 nanosheets is 1%, 2%, 5% and 10% of the total mass of the PP-CuAl2O4 composite material, which are respectively recorded as PP / CuAl 1, PP / CuAl2, PP / CuAl 5 and PP / CuAl 10.

[0074] Structural characterization and performance testing

[0075] Mechanical properties test: The prepared dumbbell-shaped PP-CuAl2O4 composite material specimens were placed on a universal material testing machine of model AI-7000-MUI produced by High-speed Railway Testing Instruments (Dongguan) Co., Ltd. to test the mechanical properties of the composite material. During the test, the tensile rate was set to 50 mm / min.

[0076] Flame retardant performance test: The prepared granular PP-CuAl2O4 composite material was placed in a cone calorimeter, set to a rated power of 35 kW, and then ignited to investigate the ignition time, peak release rate during combustion, average specific extinction area and average mass loss rate of the prepared composite material.

[0077] X-ray Photoelectron Spectroscopy (XPS)

[0078] In order to further study the chemical composition of CuAl2O4 nanosheets, the prepared CuAl2O4 nanosheets were subjected to XPS full spectrum analysis, and each element in the CuAl2O4 nanosheets was scanned in detail. The test results are as follows: Figure 1 shown.

[0079] Figure 1 The XPS spectrum of CuAl2O4 nanosheets. 2p By performing Gaussian peak separation, the binding energy can be fitted into four peaks: for CuAl2O4 nanosheets, these four peaks are at 934.8eV, 941.9eV, 954.7eV and 962.1eV. The binding energy peaks at 934.8eV and 954.7eV correspond to Cu 2p 3 / 2 and Cu 2p 1 / 2 , and the binding energies at 941.9eV and 962.1eV represent Cu 2p The above results confirm that the Cu element in CuAl2O4 nanosheets exists in a +2 valence state. 2p The corresponding peak is 74.0 eV, and the O element corresponds to three peaks at 533.1 eV, 532.0 eV, and 531.0 eV. These characteristics are similar to those of CuAl2 The corresponding spectrum of O4 is consistent.

[0080] Figure 2 is the XRD pattern of CuAl2O4 nanosheets. Figure 3 It is the XRD standard card of CuAl2O4 (JCPDS No.33-0448). Comparing the XRD spectrum of CuAl2O4 with the standard card, all the characteristic diffraction peaks shown in the XRD spectrum match the standard card. There are characteristic diffraction peaks at 2θ=31.3°, 36.8°, 44.9°, 55.7°, 58.4°, and 65.3°, which correspond to the (220), (311), (400), (422), (511), and (440) diffraction crystal planes of CuAl2O4, respectively.

[0081] Transmission electron microscopy-energy dispersive spectroscopy (HRTEM-EDS)

[0082] Figure 4 This is the HRTEM-EDS spectrum of CuAl2O4. The CuAl2O4 nanosheets were tested by high-angle annular dark field (HAADF). Figure 4 (a) is a high-angle annular dark field image of a CuAl2O4 nanosheet (the letters in the upper left corner of (a) are HAADF). Figure 4 (b) in the figure and (c) in the figure are the atomic distribution diagrams of Cu and Al elements, respectively. It can be seen that Cu and Al elements are in a relatively uniform dispersion state. Figure 4 (d) is the atomic distribution diagram of the O element, showing a tightly packed and concentrated state. The spectrum shows that the corresponding observation area contains Cu, Al, O and other elements at the same time, which further verifies the coexistence of Cu, Al, and O elements in CuAl2O4 nanosheets. The above results are consistent with the results of XPS and XRD, and together prove the successful preparation of CuAl2O4 nanosheets.

[0083] The mechanical properties of the PP material and the PP-CuAl2O4 composite materials prepared in Examples 2 to 6 were tested. The test results are shown in Tables 1 and Figure 5 shown.

[0084] Table 1 Tensile properties parameters of PP and PP-CuAl2O4 composites

[0085] sample Tensile strength(MPa) Elongation at break (%) PP 31.4 524 PP / CuAl0.2 33.5 494 PP / CuAl1 36.1 475 PP / CuAl2 38.2 317 PP / CuAl5 43.0 170 PP / CuAl10 47.7 16

[0086] Figure 5Table 1 shows the typical stress-strain curves of PP and polypropylene-copper aluminate (PP-CuAl2O4) composite materials. Table 1 shows the tensile performance parameters of PP and PP-CuAl2O4 composite materials. As shown in Table 1, the tensile strength of pure PP is 31.4MPa, and the elongation at break is 524%; the tensile strength of PP / CuAl 1 is 36.1MPa, and the elongation at break is 475%; the tensile strength of PP / CuAl 2 is 38.2, and the elongation at break is 317; the tensile strength of PP / CuAl 5 is 43.0MPa, and the elongation at break is 170%. It can be seen that with the gradual increase of the amount of CuAl2O4 added, the tensile strength of the PP-CuAl2O4 composite material gradually increases, while the elongation at break gradually decreases. Figure 5 The stress-strain curve of is a perfect reflection of this point. However, the elongation at break of PP / CuAl 10 suddenly drops to only 16%. This is because with the addition of 10% CuAl2O4, the polymer (the amount of nanomaterials added increases, and due to its large surface energy, it tends to agglomerate, thereby reducing energy and forming a stable state, resulting in worse dispersion, which in turn affects the performance of the prepared composite material) agglomerates, the dispersion becomes worse, and the interface compatibility also drops sharply, so it has a relatively large brittle performance.

[0087] Flame retardant performance study

[0088] Cone calorimetry is widely used to evaluate the combustion performance of polymer composites. Figure 6 For PP and PP-CuAl2O4 composite materials at 35kW / m 2 The heat release rate curve at 20° is shown in Table 2. The experimental data of cone calorimeter test on PP and PP-CuAl2O4 composite materials are shown in Table 2. Figure 6 It can be seen from the curve that the heat release curve of the PP composite material is a parabolic trajectory curve that first increases, reaches a peak and then gradually decreases, and gradually decreases with the increase of CuAl2O4wt%. After the pure PP is ignited, the combustion speed is accelerated, and the peak heat release (PHRR) reaches 1137±20kW / m 2 After adding CuAl2O4 nanosheets, the PHRR decreased significantly, and the PHRR of PP / CuAl 0.2 reached 610±16kW / m 2 , which is 47.2% lower than that of pure PP, and gradually decreases with the increase of CuAl2O4wt%. The PHRR of PP / CuAl 10 is only 380±7kW / m 2 This shows that the composite of CuAl2O4 nanosheets and PP greatly reduces the combustion heat release of the material and can effectively reduce the hazard of fire.

[0089] Table 2 Experimental data of cone calorimeter test on PP and PP-CuAl2O4 composites

[0090] sample TTI(s) <![CDATA[PHRR(kW / m 2 )]]> <![CDATA[ASEA(m 2 / kg)]]> AMLR(g / s) PP 40±3 1137±20 336±11 0.064±0.005 PP / CuAl0.2 44±4 610±16 286±9 0.055±0.004 PP / CuAl1 48±3 489±12 239±8 0.051±0.004 PP / CuAl2 51±4 428±8 226±8 0.045±0.003 PP / CuAl5 58±4 404±9 188±7 0.037±0.003 PP / CuAl10 63±3 380±7 165±6 0.032±0.003

[0091] TTI: time to ignition; PHRR: peak release rate; ASEA: average specific extinction area; AMLR: average mass loss rate.

[0092] When CuAl2O4 is added, the average specific extinction area (ASEA) and average mass loss rate (AMLR) values ​​are significantly lower than those of pure PP, and gradually decrease with the increase of CuAl2O4wt%, while the ignition time (TTI) increases accordingly. The TTI of PP is 40±3s, and the ASEA is 336±11(m 2 / kg), AMLR is 0.064±0.005; while for PP / CuAl 10 sample, TTI is 63±3s, ASEA is 165±6(m 2 / kg), and AMLR was 0.032±0.003. Compared with pure PP, TTI was delayed by 23s, PHRR was reduced by 51.9%, and AMLR was reduced by 50.0%. These data indicate that the incorporation of CuAl2O4 nanosheets significantly improved the flame retardant properties of PP.

[0093] Figure 7 Digital photos of the residues after cone calorimeter test, PP (a), PP / CuAl1 (b) and PP / CuAl10 (c). After cone calorimeter test on PP, PP / CuAl 1 and PP / CuAl 10, Figure 7 Digital photos of. Figure 7 (a) is a digital photo of PP residues, showing irregular and locally dense arrangement; Figure 7 (b) is a digital photo of PP / CuAl residues, showing a uniformly dispersed particle arrangement; Figure 7 (c) is a digital photo of the residue of PP / CuAl 10, showing a uniform, tight and regular particle arrangement. It can be clearly observed that there are tiny and dense residual substances after the addition of CuAl2O4 nanosheets. PP / CuAl 1(b) has more residual carbon than PP(a), and PP / CuAl 10(c) has the most residual carbon and residual substances.

[0094] In summary, in the preparation of copper aluminate, Cu(NO3)2·3H2O, Al(NO3)3·9H2O and NaOH were used as raw materials and the chemical coprecipitation method was used to synthesize nano CuAl2O4 powder. The structure of copper aluminate was confirmed by X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction analysis (XRD), transmission electron microscopy X-ray energy spectrum analysis (HRTEM-EDS) and other methods.

[0095] Mechanical properties research shows that with the gradual increase of CuAl2O4 nanosheet incorporation amount, the tensile strength of PP-CuAl2O4 composite materials gradually increases, while the elongation at break gradually decreases.

[0096] The flame retardant performance study shows that the composite of CuAl2O4 nanosheets and PP greatly reduces the heat release peak of the material, effectively delays the ignition time, and can effectively improve the flame retardant properties of PP.

[0097] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing copper aluminate nanosheets, characterized in that: The following steps are involved: Mixing a soluble copper salt, a soluble aluminum salt, water and an alkaline solution to perform a coprecipitation reaction to obtain a precipitated product; The precipitation product is calcined to obtain the copper aluminate nanosheets.

2. The preparation method according to claim 1, characterized in that: The molar ratio of copper in the soluble copper salt to aluminum in the soluble aluminum salt is 1:(1.5-3).

3. The preparation method according to claim 1 or 2, characterized in that: The coprecipitation reaction is carried out at a temperature of 80 to 150° C. and for a time of 0.5 to 2 hours.

4. The preparation method according to claim 1 or 2, characterized in that: The alkaline solution includes a solution of an alkali metal hydroxide.

5. The preparation method according to claim 1 or 2, characterized in that: The calcination temperature is 500-800° C. and the calcination time is 2-6 hours.

6. The copper aluminate nanosheets prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The copper aluminate nanosheet has a sheet diameter of 30 to 60 nm and a thickness of 5 to 15 nm.

7. A polypropylene-copper aluminate composite material, characterized in that: It comprises a polypropylene matrix and copper aluminate nanosheets dispersed in the polypropylene matrix; the copper aluminate nanosheets are the copper aluminate nanosheets according to claim 6.

8. The polypropylene-copper aluminate composite material according to claim 7, characterized in that: The mass of the copper aluminate nanosheets is 0.2-10% of the mass of the polypropylene-copper aluminate composite material.

9. The method for preparing the polypropylene-copper aluminate composite material according to claim 7 or 8, characterized in that: The method comprises the following steps: melt-blending a polypropylene matrix and copper aluminate nanosheets to obtain the polypropylene-copper aluminate composite material.

10. Use of the polypropylene-copper aluminate composite material according to claim 7 or 8 or the polypropylene-copper aluminate composite material prepared by the preparation method according to claim 9 in the field of flame retardancy.